2021
DOI: 10.1021/acsnano.0c09386
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Assembly of Functional Peptides with Divergent Programming Elements

Abstract: Self-assembling peptides are being applied both in the biomedical area and as building blocks in nanotechnology. Their applications are closely linked to their modes of self-assembly, which determine the functional nanostructures that they form. This work brings together two structural elements that direct nanoscale self-association in divergent directions: proline as a β-breaker and the β-structure-associated diphenylalanine motif, into a single tripeptide sequence. Amino acid chirality was found to resolve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 71 publications
2
79
0
Order By: Relevance
“…In the case of F D FF, the hydrophobicity appears similar to FFF; however, three phenyl rings in F D FF cannot achieve co-planarity due to steric complications as a result of a chiral mismatch. 38 Screening of Coulomb repulsions does not affect sterical barrier resulting in almost no effect of salt addition on CAC value of F D FF.…”
Section: Papermentioning
confidence: 99%
“…In the case of F D FF, the hydrophobicity appears similar to FFF; however, three phenyl rings in F D FF cannot achieve co-planarity due to steric complications as a result of a chiral mismatch. 38 Screening of Coulomb repulsions does not affect sterical barrier resulting in almost no effect of salt addition on CAC value of F D FF.…”
Section: Papermentioning
confidence: 99%
“…Single‐crystal and molecular dynamics simulations revealed that the different intermolecular interactions of each isomer were responsible for long‐range, medium‐range, or short‐range assemblies. [ 33 ]…”
Section: D‐amino Acid‐based Peptide Nanostructuresmentioning
confidence: 99%
“…Amyloid-associated disorders constitute a large and diverse class of pathological states of growing societal concern, as the increasing life expectancy is leading to an increasing aged population, and consequent occurrence of amyloidoses. Amongst the many potential treatments, NPs have attracted growing interest as inhibitors of amyloid aggregation, including those formed by peptides [206], carbon nanostructures [207], gold [208], and also ceria. In particular, ceria NPs were shown to bind to the α-synuclein monomer and extend the lag phase time of amyloid fibril formation, and the resulting aggregates are relatively less toxic than those formed in the absence of ceria [209].…”
Section: Amyloidosis Inhibitionmentioning
confidence: 99%